Tindak Tutur Ekspresif pada Program Kompetisi Pendidikan Academy of Champions by Ruangguru (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2026)
Speech acts are actions or processes performed by speakers to convey messages and information to their interlocutors using language as a medium. This study examines one type of speech act, namely expressive speech acts. This study aims to classify and identify the types of expressive speech acts in episodes 1 to 5 of the Academy of Champions, a program from the Ruangguru educational competition, which was uploaded to YouTube. This study uses a qualitative descriptive method with a pragmatic approach. Data were collected using the free listening and note-taking techniques, as the researcher was not directly involved in the event. Data analysis was conducted using the pragmatic matching technique, in which the speaker and interlocutor served as the primary tools for interpretation. The data are presented formally in tables and informally in narratives. The results of the study on expressive speech acts in the educational competency program in the Academy of Champions by Ruangguru video found 198 expressive speech acts consisting of 10 types, namely saying thank you (28 utterances), congratulating (7 utterances), blaming (6 utterances), praising (71 utterances), belittling (11 utterances), feeling guilty (9 utterances), complaining (28 utterances), apologizing (13 utterances), greeting (16 utterances), and feeling proud (9 utterances). Praise speech acts are the most dominant type found in this study. The results of this study are expected to provide an understanding of and knowledge in the field of pragmatics, serving as a valuable source of information for students to analyze expressive speech acts further.